2018
DOI: 10.1002/hipo.22823
|View full text |Cite
|
Sign up to set email alerts
|

Impact of adolescent stress on the expression of stress‐related receptors in the hippocampus of animals exposed to alcohol prenatally

Abstract: Many functions of the hippocampus are affected by prenatal alcohol exposure (PAE). In particular, dysregulation of the stress response is especially important because individuals with PAE carry increased risks for exposure to stressful environments throughout life. Little is known, though, about how adolescent stress in the context of PAE-related stress system dysregulation may further alter hippocampal development. Here, we investigate the short- and long-term effects of adolescent chronic mild stress (CMS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 107 publications
1
6
0
Order By: Relevance
“…PAE-induced dysregulation of these key receptor systems may predispose individuals to the adverse effects of stress over the life course and increase vulnerability to stress-related disorders such as depression and anxiety. In support of this, we have found that chronic stress during adolescence may further alter mRNA expression of these stress-related receptors and anxiety-like behavior in PAE compared to C animals, and may do so in a sex-dependent manner (Raineki et al, 2018, 2016). As well, we recently showed that PAE and chronic stress in adulthood interact to result in sexually-dimorphic and time-dependent dysregulation of the neurocircuitry underlying behavioral, emotional and stress regulation, as well as alterations in depressive-like (forced swim test) behavior (Lam et al, 2018).…”
Section: Introductionsupporting
confidence: 57%
See 3 more Smart Citations
“…PAE-induced dysregulation of these key receptor systems may predispose individuals to the adverse effects of stress over the life course and increase vulnerability to stress-related disorders such as depression and anxiety. In support of this, we have found that chronic stress during adolescence may further alter mRNA expression of these stress-related receptors and anxiety-like behavior in PAE compared to C animals, and may do so in a sex-dependent manner (Raineki et al, 2018, 2016). As well, we recently showed that PAE and chronic stress in adulthood interact to result in sexually-dimorphic and time-dependent dysregulation of the neurocircuitry underlying behavioral, emotional and stress regulation, as well as alterations in depressive-like (forced swim test) behavior (Lam et al, 2018).…”
Section: Introductionsupporting
confidence: 57%
“…CRHR1 mRNA and protein expression are also decreased in the hippocampus of adolescent PAE males (Caldwell et al, 2015; Raineki et al, 2018). Additionally, PAE decreases MR mRNA expression in the adult female hippocampus (Sliwowska et al, 2008; Uban et al, 2013), and alters hippocampal MR mRNA expression in adolescent male and GR mRNA expression in adolescent female rats (Raineki et al, 2018). PAE-induced dysregulation of these key receptor systems may predispose individuals to the adverse effects of stress over the life course and increase vulnerability to stress-related disorders such as depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, studies conducted in rats and voles have revealed modest contributions of stress in normal and awake animals after an acclimation procedure (Liang, King, & Zhang, 2011, 2012; Reed, Pira, & Febo, 2013; Yee et al, 2016). However, changes in the sensitivity of stress-related circuitry including the hippocampus and the hypothalamic-pituitary-adrenal (HPA) axis following PAE are well documented (Hellemans, Verma, Yoon, Yu, & Weinberg, 2008; Lam, Raineki, Ellis, Yu, & Weinberg, 2018; Raineki, Ellis, & Weinberg, 2018), and carry the potential to introduce a different set of confounds in an awake scanning procedure. Next, animals in this investigation reached adulthood by the time image acquisition was conducted.…”
Section: Discussionmentioning
confidence: 99%